PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V A SD NEGERI 61 HARAPAN BARU - Warsini '; Zariul Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : this research was conducted because of the result of learning social IPA study class Va SD Negeri 61 Harapan Baru. from 22 students who achieve KKM just 3 students (13,68%) while students who did’nt complete 19 students (86,36%) with an average of 54,40. The purpose of this research to improve learning outcomes IPA class Va SD Negeri 61 Harapan Baru with the application of learning models Contextual Teaching Learning (CTL) the results obtained by the average value of 54,40 basic score increased in the first cycle of 25,23% to 73,27% in the second cycle the average value of students also increased by 18,87% to 79,63%. On the basis of completeness score IPA students learning outcomes is only 54,40%(not finished). After the professor of applied learning model Contextual Teaching Learning (CTL) in the first cycle classical completeness increased to 13,27%(not finished) the second cycle of classical completeness obtained are increased to increase to 100%. Activities of teachers at the first meeting of 62,50% with both categories. The second meeting increased to75% in both categories. In the second cycle increased to 84,37% with the category very well. At a meeting of the second meeting of the second cycle,the activities of teacher increased to  97,57% with the category very well. Activities of students in the first cycle of the first meeting activity students acquire a percentage of 64,54% in both categories. The second meeting of the first cycle to 68,40%  in both categories. At the first meeting of the second cycle of student activity increased to 74,97% with the categoryvery well,and the second meeting of the second cycle increased again to  78,32% with the category very well. Key words : Contextual Teaching Learning (CTL),learning outcomes IPA